ChemInform Abstract: Cyanative Self‐Condensation of Aromatic Aldehydes Promoted by VO(OiPr)3—Lewis Base as a Cooperative Catalyst. Issue 21 (2nd May 2013) - Kodama, Koichi; Kawamata, Hiroaki; Takahashi, Naoya; Hirose, Takuji
Abstract It is crucial that the reaction is carried out in oxygen atmosphere to afford the products selectively.